Investigation into Influences of Hydraulic Fracturing for Hard Rock Weakening in Underground Mines - Cao, Xu; Wu, Saisai; He, Qingyuan (Applied sciences, 2024)
The long overhanging distance of hard roofs and long-collapse steps induces a large area of suspension on the working face in underground coal mines, resulting in excessive pressure and deformation on the surrounding rocks of the adjacent roadway in the work face, which seriously threatens the safety of coal mining operations. In this study, in order to study the hydraulic fracturing effects on hard roofs, numerical simulation and in situ tests were conducted. The analysis and comparison of fracturing effects under different hydraulic fracturing parameters were carried out, and the reasonable hydraulic fracturing parameters of the hydraulic weakening of hard roofs were designed accordingly. Based on designed hydraulic fracturing, industrial tests were conducted in the field while stress and deformation were recorded. The results show that hydraulic fracturing could effectively reduce the pressure of the hard roof. Hydraulic fracturing effectively destroyed the cantilever beam structure above the coal pillar, reduced the stress concentration, and moderated mineral pressure at the working face. The proposed methods and obtained results provide theoretical and technical support for the treatment of underground mines with hard roofs.